2022
DOI: 10.3389/fpubh.2022.971115
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and influencing factors of pandemic fatigue among Chinese public in Xi'an city during COVID-19 new normal: a cross-sectional study

Abstract: ObjectiveThis study aimed to assess Chinese public pandemic fatigue and potential influencing factors using an appropriate tool and provide suggestions to relieve this fatigue.MethodsThis study used a stratified sampling method by age and region and conducted a cross-sectional questionnaire survey of citizens in Xi'an, China, from January to February 2022. A total of 1500 participants completed the questionnaire, which collected data on demographics, health status, coronavirus disease 2019 (COVID-19) stressors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 50 publications
2
13
1
3
Order By: Relevance
“…Finally, a slightly significant positive correlation was found between anxiety related to COVID-19 and pandemic fatigue, which is consistent with previous studies [ 39 ]. Previous studies on the psychological impacts of the pandemic have suggested that feelings of stress and anxiety related to the virus were common [ 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…Finally, a slightly significant positive correlation was found between anxiety related to COVID-19 and pandemic fatigue, which is consistent with previous studies [ 39 ]. Previous studies on the psychological impacts of the pandemic have suggested that feelings of stress and anxiety related to the virus were common [ 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…The current systematic review and meta-analysis sought to investigate the correlates and psychometric properties of the C-19ASS. The C-19ASS exhibited a consistent factor structure and acceptable reliability in Brazilian (Coelho et al, 2022), Chinese (Xin et al, 2022), Greek (Seydavi et al, Unpublished), Indonesian (Muthiah et al, 2022), Iranian (Akbari, Seydavi, et al, 2021), Italian (Mansueto et al, 2022), Saudi Arabian (Alhakami et al, 2023), Turkish (Obu ca et al, Unpublished) and US (Nikčevi c & Spada, 2020) populations. In addition, it has been studied concerning a vast array of variables, as described above, which makes it a promising tool for assessing COVID-19-pandemic-related psychopathology.…”
Section: Discussionmentioning
confidence: 95%
“…The current study sought to investigate the psychometric properties of the C‐19ASS through a meta‐analysis/systematic review. The measure has been broadly welcomed, leading to its use in Brazilian (Coelho et al, 2022), Chinese (Xin et al, 2022), Greek (Seydavi et al, 2023), Indonesian (Muthiah et al, 2022), Iranian (Akbari, Seydavi, et al, 2021), Italian (Mansueto et al, 2022), Saudi Arabian (Alhakami et al, 2023), Turkish (Obuća et al, Unpublished) and US (Nikčević & Spada, 2020) populations. Generally, good psychometric properties were reported across these different populations.…”
Section: Introductionmentioning
confidence: 99%
“…Older age, wider pulse pressure, male sex, low rank, non-metropolitan location, alcohol consumption and smoking are associated with increased risk of MetS in this study, which was consistent with the findings of previous studies. 15,19,35,[47][48][49][50] Male police officers had significantly increased odds of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 97%